Passionate refrains: the theatricality of Urdu on the Parsi stage. Issue 3 (2nd July 2016) - Hansen, Kathryn
ABSTRACT: The Parsi theatre is known to have contributed to early Indian cinema textual legacies of story and theme, genre and star roles. It also supplied technical expertise, personnel, and capital vital to the new industry. I argue that the aesthetic sensibility associated with the Urdu language was also of great importance, especially to the emergence of the Islamicate idiom in Bombay cinema. Beginning with the popular pageant, the Indar Sabha, Parsi theatrical companies embraced the poetics of the Urdu ghazal with its declarations of ishq (passion) and recurring radifs (refrains). Why did Urdu win out over English and Gujarati as the dominant language of the then Bombay-based theatre? The analysis traces the contribution of Urdu munshis (playwrights), who together with their more illustrious actor-manager employers, co-created a distinctive Parsi-Urdu theatrical style. The performance of Urdu poetry together with Hindustani music and dance is seen as enhancing the literary appeal and musicality of new dramas, imparting a commercial advantage. Moreover, changes in playhouse design and the conventions of melodrama called for a forceful, rhythmic style of delivery, for which actors trained in Urdu were well suited. The article concludes with a case study of Agha Hashr Kashmiri, author of countless dramas and screeplays, focusing on his historical allegory, Yahudi ki Larki, which was made into a well-known Bombay film in 1955.